Penerapan Strategi Digital Marketing dan Promotion Mix pada UMKM Berry Catszone Batam - Abd. Rohim Alamsyah; Golan Hasan (Jurnal Pengabdian Masyarakat Akademisi, 2022)
This service program involves one of the MSME partners in Batam City, namely Berry Catszone Batam. At the moment, partners issues only pertain to offline sales. The online sales system is still very limited and only relies on consumers who have settled or subscribed. This situation results from partners ignorance of the value of apllying digital strategies and using digital technology to run a corporation. This issue can be resolved by giving partners guidance and input through the use social media's built-in features, the creation of e-catalog and business growth promotion efforth. The activities are designed to improve business actors' understanding how to implement digital marketing strategies and the value of running promotions, which is expected to improve sales turnover and increase brand awareness as among public at large. The mentoring method is the one employed in this project. As a result of this volunteer activities, a catalog was created on the WhatsApp Business account, flyers were created for various kinds of promotions, and digital strategies were employed to encourage more active usage of instastories and other social media features